Analysis Of Sharia Financial Literature Post Merger Of Sharia Commercial Bank Pekanbaru - Souvya Fithrie; Idel Waldelmi; Afvan Aquino (UIN Siber Syekh Nurjati Cirebon, 2022)
Islamic financial literacy in Islamic financial institutions in the city of Pekanbaru, from the data revealed that the level of Islamic financial literacy of Indonesian Islamic bank customers, can be stated in good condition and high interest in using Islamic financial services, this is stated in the results of the study with an average the average level of Islamic financial literacy is in the good category (3.8). The data reveals that from Sharia financial literacy on knowledge, trust and skills, it reveals that the data reveals the level of public trust is also classified as good/high. This research was conducted on customers of Indonesian Islamic banks in Pekanbaru city. The type of this research is qualitative research.Keywords: Islamic Financial LiteracyÂ